The Relationship Between Fear of Missing Out and Internet Gaming Disorder in Gacha Game Players - Utama, Brigit; Rahayu Hardianti Utami (In Trend : International Journal of Trends in Global Psychological Science and Education, 2024)
Gacha is a game system for getting characters or items in video games using virtual currency. However, on average, existing gacha games have a limited gacha schedule, meaning that players have a limited time to get them. This can influence the emergence of fear of missing out and internet gaming disorder in gacha game players. This research aims to see the correlation between fear of missing out and internet gaming disorder in gacha game players. The research sample consisted of 101 individuals selected using purposive sampling techniques. Data collection was conducted using the fear of missing out and internet gaming disorder scales. Data analysis using the Pearson technique shows that there is a significant and positive relationship between fear of missing out and internet gaming disorder with a correlation coefficient of 0.575